HUBUNGAN EFIKASI DIRI DENGAN KEMANDIRIAN BELAJAR SISWA KELAS IV SEKOLAH DASAR NEGERI DI KELURAHAN PALMERAH JAKARTA BARAT - Litha Ayu Ningsih; Taofik; Banindra Yudha, Chrisnaji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the relationship between self-efficacy and learning independence among fourth-grade students at public elementary schools in Palmerah Subdistrict, West Jakarta. This study employed a quantitative approach with a correlational method. The population consisted of 238 fourth-grade students from public elementary schools in Palmerah Subdistrict, West Jakarta. The samples were selected using proportional random sampling, resulting in 149 students proportionally drawn from each school. Data were collected using self-efficacy and learning independence questionnaires that had been tested for validity and reliability. The data analysis techniques included descriptive statistics, normality test, linearity test, correlation coefficient test, correlation significance test, and coefficient of determination test. The results showed a positive and significant relationship between self-efficacy and learning independence, as indicated by a significance value of 0.000 (p < 0.05) and a correlation coefficient of 0.541, which falls into the moderate category. Furthermore, the coefficient of determination value of 0.293 indicated that self-efficacy contributed 29.3% to students' learning independence. Therefore, self-efficacy is an important factor associated with the learning independence of fourth-grade students at public elementary schools in Palmerah Subdistrict, West Jakarta.